Endovascular treatment of traumatic iliac venous injury combined with phlegmasia cerulea dolens in Korea: a case report - Suyoung Park; Jeong Ho Kim; Jung Han Hwang; Jayun Cho (Journal of Trauma and Injury)
Traumatic iliac venous injury is rare but can be fatal. Although surgical management is considered a primary treatment method, urgent treatment is required when deep venous thrombosis and subsequent phlegmasia cerulea dolens is combined. It is difficult to treat by surgical management, and pharmaceutic thrombolysis cannot be applied due to the trauma history. Here, we describe a case of unilateral traumatic iliac venous injury and subsequent diffuse venous thrombosis in the affected iliofemoral and infrapopliteal veins, combined with phlegmasia cerulea dolens, treated with endovascular management, including bare metal stent insertion and aspiration thrombectomy.